Non-optical coherence tomography modalities for assessment of angle closure - Natalia Porporato; Katharina C Bell; Shamira A Perera; Tin Aung (Taiwan Journal of Ophthalmology, 2022)
Primary angle closure glaucoma is a leading cause of irreversible blindness, particularly in Asia. Its pathophysiology is based in the closure of the anterior chamber angle (ACA). In addition to gonioscopy (current reference standard), in the past decade, anterior segment optical coherence tomography (AS-OCT) has been incorporated in routine ophthalmic practice to help assess the configuration of the ACA. Especially in nonspecialist ophthalmology practice, gonioscopy may be less frequently performed and AS-OCT may not be available, leading to the need of other anterior segment evaluation methods. Evaluating the anterior chamber depth (ACD) has long been recognized as screening tool for primary angle-closure glaucoma. It can be measured with several devices, such as Scheimpflug photography and the scanning peripheral ACD analyzer. It can also be estimated with the oblique flashlight test and van Herick technique (limbal ACD assessment). More recently, goniophotographic systems have been developed to produce images of the ACA similar to those seen with manual gonioscopy. NGS-1 automated gonioscope (NIDEK Co, Gamagori, Japan) and the RetCam (Natus Medical Incorporated, Pleasanton, CA) are commercially available. However, NGS-1 is the only one with a specialized software for ACA imaging. Several prototype devices are currently being developed, such as the GonioPEN and axicon lens assisted gonioscopy. This article aims to review different modalities of ACA assessment, beyond AS-OCT, and compare their relative advantages and disadvantages.